TAX RATES AND ADOPTION OF IFRS ON FOREIGN DIRECT INVESTMENT in ASEAN ECONOMIC COMMUNITY COUNTRIES - Pertiwi, Rahma Kamalia; Nazar, Shinta Ningtiyas (EAJ (Economic and Accounting Journal), 2019)
Research aim : This study aimed to get empirical evidence of the effect of tax rates and the adoption of IFRS to Foreign Direct Investment (FDI). The study also attempts to identify whether a country needs to adopt IFRS fully, convergence IFRS or not using IFRS  able to increase FDI. Otherwise to detect Tax rates from Asean Economic Community Countries can affected FDI. Design / Methodology / Approach: This study uses a quantitative descriptive approach. The sample consisted of 54 observations of each variable that consists of information 9 countries of the ASEAN Economic Community (AEC) during the years 2011 to 2016. The proposed model was tested using multiple regression analysis through partial t test, as well as simultaneous test F. Research findings: The results showed the tax rate in a country negatively affect FDI and the adoption of IFRS by a country has a positive effect on FDI, while simultaneously tax rates and the adoption of IFRS have a significant effect on FDI. Contributions theoretical / Originality :  This study extends the theoretical concept of tax rates and the level of IFRS adoption, even though previous research has been done before in developing countries, and  there is no research that focuses on AEC countries.  Previous research used a simple score of 2 to 3 score levels in AECsuring the level of IFRS adoption in each sample country so that it was not able to accurately AECsure the level of IFRS adoption in each country. This Research is using five (5) levels of scores taken from the IASB namely  full adoption, adapted, pieceAECl, referenced, and not adoption at all. Practicioner / Policy Implication: The result will be useful to policy makers as an authoritative Tax and Accounting Bodies in AEC Countries as an input to identify factors which can increase Foreign Direct Investment. Research Limitation/Implication : This Study used data from 2011 to 2016, however, others factors could be used with FDI in future researches.